Effects of Vitamin D Insufficiency on Hemoglobin Levels and Skin Infections Among Libyans of Various Ages - Eman Alsqyar; Antisar Ibashouk; Nesrin Ballaq (AlQalam Journal of Medical and Applied Sciences, 2024)
This study explores the effects of vitamin D deficiency on hemoglobin levels and skin infections in 138 Libyan men and women across various ages. A cross-sections study was done in Al-Ajilat city, during the period from June to September 2024. A total of 63 (45.35 %) males and 75 (54%) females were included in this study, with different skin infections from different ages. A hematological blood analyzer (Sysmex KX-21N) was used to evaluate the hemoglobin concentration (HGB) in venous blood samples obtained in EDTA tubes. A competitive ELISA-based immunoassay was also used to assess vitamin D (25-hydroxycholecalciferol) in the patients’ serum. Vitamin D insufficiency was more prevalent in men (60.3%) than in women (49.3%), though the difference was not statistically significant (p = 0.263). Hemoglobin levels were higher in men (mean: 14.2 g/dL) than women (mean: 12.5 g/dL), reflecting potential gender-specific biological differences. Male participants also exhibited greater variability in vitamin D and inflammatory marker (CRP) levels. Infection patterns revealed gender-related trends, with fungal infections being more common in men and viral infections in women. However, the association between infection types and gender was not statistically significant (p = 0.137). Gender significantly influenced CRP and hemoglobin levels but had no apparent effect on vitamin D levels. No strong linear correlations were observed between vitamin D, CRP, hemoglobin, or age. The findings highlight gender differences in vitamin D status, immune responses, and infection types, although most differences lacked statistical significance. The study underscores the need for further research to elucidate vitamin D’s role in skin infections and its potential interplay with hemoglobin levels and immune markers تتناول هذه الدراسة تأثير نقص فيتامين د على مستويات الهيموجلوبين والالتهابات الجلدية لدى 138 رجل وامرأة ليبي في مختلف الأعمار. أجريت دراسة مقطعية في مدينة العجيلات، خلال الفترة من يونيو إلى سبتمبر 2024. تم تضمين إجمالي 63 (45.35٪) من الذكور و 75 (54٪) من الإناث في هذه الدراسة، مع التهابات جلدية مختلفة من مختلف الأعمار. تم استخدام محلل الدم الدموي لتقييم تركيز الهيموجلوبين في عينات الدم الوريدي التي تم الحصول عليها في أنابيب EDTA. كما تم استخدام اختبار المناعة القائم على ELISA التنافسي لتقييم فيتامين د (25-هيدروكسي كوليكالسيفيرول) في مصل المرضى. كان نقص فيتامين د أكثر انتشارًا لدى الرجال (60.3٪) منه لدى النساء (49.3٪)، على الرغم من أن الفرق لم يكن ذا دلالة إحصائية (ص = 0.263). كانت مستويات الهيموجلوبين أعلى لدى الرجال (متوسط: 14.2 جم / ديسيلتر) من النساء (متوسط: 12.5 جم / ديسيلتر)، مما يعكس الاختلافات البيولوجية المحتملة بين الجنسين. أظهر المشاركون الذكور أيضًا تباينًا أكبر في مستويات فيتامين د والعلامات الالتهابية. كشفت أنماط العدوى عن اتجاهات مرتبطة بالجنس، حيث كانت العدوى الفطرية أكثر شيوعًا لدى الرجال والعدوى الفيروسية لدى النساء. ومع ذلك، فإن الارتباط بين أنواع العدوى والجنس لم يكن ذا دلالة إحصائية (ص = 0.137). أثر الجنس بشكل كبير على مستويات العلامات الالتهابية والهيموجلوبين ولكن لم يكن له تأثير واضح على مستويات فيتامين د. لم يتم ملاحظة أي ارتباطات خطية قوية بين فيتامين د أو العلامات الالتهابية أو الهيموجلوبين أو العمر. تسلط النتائج الضوء على الاختلافات بين الجنسين في حالة فيتامين د والاستجابات المناعية وأنواع العدوى، على الرغم من أن معظم الاختلافات تفتقر إلى الدلالة الإحصائية. تؤكد الدراسة على الحاجة إلى مزيد من البحث لتوضيح دور فيتامين د في التهابات الجلد وتفاعله المحتمل مع مستويات الهيموجلوبين والعلامات المناعية